KEHIDUPAN BIDUAN HIBURAN MALAM (STUDI KASUS BIDUAN KEYBOARD BONGKAR DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU) - Ajeng Oksa Winanda; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Fondness on entertainment such as music turns out to be a lifestyle, especially the amusement of music such as a amusement of keyboard, and plus the existence of singers who are scantily clad and very sexy. With spurred by the difficulty of finding employment, poverty, powerlessness, also a moral weakness so no other choice for a living besides being a singer is not necessary capital and skill. As teenagers in District Rengat Indragiri Hulu on average still sitting in school from junior high to high school to become a singer. Way of dressed unwrapped at the time of the performing is far from the norm. And it is very unfortunate in this case the role of the parents who are supposed to supervise their children's behavior even support such action, even if the parents are proud of her son become a singer. The purpose of this study was to determine the background of the life of the singers in the keyboard bongkar and the view of singers keyboard bongkar about activity of the evening entertainment and what reason they survive.The theory used is the theory of social deviation, exchange theory, the theory of social change. This research is a qualitative descriptive study using sampling purposive method, data collection by interview, observation and literature study. The number of respondents in this study were as many as 10 people, 8 keyboard bongkar singers and 2 supporters informant.Based on research that has been done can be concluded that the encouragement for the youth in the District Rengat Indragiri Hulu became a choir director at the amusement of keyboard mostly due to economic problems, the influence of lifestyle and a lack of oversight and guidance of the parents. background of the teens who became keyboard bongkar singers that average came from a family of middle economy. Consequence of the profession who undertaken by teenager in addition to bringing money to meet its needs and can funnel their hobby, the profession also brings good assumptions of society, especially the view of the men who underestimate that their profession.Keywords: Life of Singer, Nightlife, Keyboard Bongkar